Factors Influencing Earthquake Resistance in Vernacular Architecture: A Systematic Literature Review of Architecture Indigenous Knowledge - Riza Aulia Putra; Dewi Larasati; Aswin Indraprastha; Hanson E Kusuma (DIMENSI (Journal of Architecture and Built Environment), 2025)
Vernacular architecture in seismic-prone regions often reflects generations of  knowledge embedded in local building practices. This knowledge contributes significantly to the earthquake resilience of traditional structures through context-specific design strategies and materials. This study presents a systematic literature review to identify the critical factors that influence the seismic resistance of vernacular buildings. A summative content analysis method was employed, emphasizing the elements that affect the seismic performance of these structures. The review identifies six key factors contributing to the earthquake resistance of vernacular buildings, categorized into two primary domains: explicit knowledge, which includes building typology, structural systems, construction methods, and building materials, and implicit knowledge, encompassing community involvement and risk management. The findings underscore the significance of local architectural knowledge as a fundamental basis for developing more effective and sustainable construction strategies to enhance earthquake resilience in earthquake-prone areas.